Understanding The E-Banking Adoption on MSMEs: An UTAUT Approach - Amir Mustolih; Arya Samudra Mahardhika (Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study analyzes the acceptance and use of e-banking among MSMEs in Kebumen Regency using the UTAUT model approach. The UTAUT model suggests that the factors that play an important role in user acceptance include job expectations, business expectations, social influences, and facilitating conditions. This type of research is quantitative research and the data source used is primary data. The sampling technique in this study was using purposive sampling. Respondents in this study were 50 MSME actors in Kebumen Regency who already used e-banking. The hypothesis in this study was tested using SEM-PLS with WarpPLS 7.0. The results in this study indicate that the first model, namely performance expectancy, effort expectancy, and social influence are factors that influence behavioral intention. The second model of behavioral intention is a factor that affects Use behavioral, while facilitating conditions do not affect Use behavioral in the use of e-banking for MSMEs in Kebumen Regency.